Effects of climate warming and elevated CO2 on autotrophic nitrification and nitrifiers in dryland ecosystems. (January 2016) - Hu, Hang-Wei; Macdonald, Catriona A.; Trivedi, Pankaj; Anderson, Ian C.; Zheng, Yong; Holmes, Bronwyn; Bodrossy, Levente; Wang, Jun-Tao; He, Ji-Zheng; Singh, Brajesh K.
Abstract: Global climate change is predicted to enhance atmospheric temperature and CO2, with important consequences on biogeochemical nitrogen cycling in dryland ecosystems, which are highly vulnerable and characterized by extremely low nutrient availability. Belowground nitrification processes, predominantly mediated by ammonia-oxidizing archaea (AOA) and bacteria (AOB), are central to plant nitrogen availability and soil N2 O emissions, but their responses to future climatic scenarios in drylands remain largely unknown. Here we investigated the impact of factorial combinations of elevated CO2 (+200 ppm) and elevated temperature (+3 °C) on dynamics of ammonia oxidizers and nitrification in three dryland soils planted with Eucalyptus tereticornis . Soil properties (including total carbon, H2 O%, and nitrate) and potential nitrification rates were strongly impacted by elevated temperature after nine months, accompanied by significantly higher AOA abundance in two soils and a gradual decrease in AOB abundance under elevated temperature. DNA-stable isotope probing showed increased assimilation of 13 CO2 by AOA, but not AOB, under warming, indicating that AOA were actively growing and utilizing the 13 CO2 substrates, which was coupled with significantly higher net nitrogen mineralization and nitrification rates. High-throughput microarray analysis revealed temperature selections of particular AOA assemblages and a significant reduction in diversity and co-occurrence of the metabolically active AOA phylotypes. Although these responses were soil specific, structural equation modelling by compiling all the data together showed that warming had significant direct and indirect impacts on soil nitrification which were driven by changes in AOA community structure, but no obvious effects of elevated CO2 could be identified. Our findings suggest that warming has stronger effects than elevated CO2 on autotrophic nitrification, and AOA are more responsive to elevated temperature than AOB in the tested dryland ecosystems. Graphical abstract: Highlights: A full factorial design of elevated temperature and elevated CO2 was established. Effects of elevated temperature on nitrification and nitrifiers were soil-dependent. No significant effect of elevated CO2 was found on nitrification. AOA were more responsive to elevated temperature than AOB. AOA are the dominant nitrifiers in the tested dryland soils.